Discussion of the Characteristics of Physical Activity - Wang, Shaohua; Chen, Chao (Journal of Theory and Practice of Contemporary Education, 2024)
this article through logical thinking and generalizations, discusses the characteristic of sports activities, and argues that the characteristics of the sports activities can undertake interpretation from four dimensions, respectively, was based on the physical activity of the basic means and form, for the purpose of one's own development, with the same subject as the existence and value orientation of humanistic spirit. Comprehensive and in-depth understanding of the characteristics of sports activities is the foothold of constructing the sports science in the new era, and also the starting point of the sports science in the new era facing the future and going to the world. Design a curriculum that integrates vocational English vocabulary with relevant industry- specific content. Ensure that the curriculum includes authentic materials, contextualized vocabulary, and opportunities for active learning.